Clinical and epidemiological profile of patients with multiple sclerosis in Uberaba, Minas Gerais, Brazil - Sônia Beatriz Félix Ribeiro; Danilo Fonseca Maia; João Batista Ribeiro; Fabrízio Antônio Gomide Cardoso; Cátia Silva (Arquivos de Neuro-Psiquiatria)
Multiple sclerosis (MS) is an immune-mediated disease that affects the central nervous system. Clinical presentation and prevalence vary widely around the world. OBJECTIVE: To describe the clinical and epidemiological aspects of patients with MS in Uberaba (MG). METHOD: We conducted a transversal descriptive study, with data analysis of 35 patients with MS. RESULTS: Prevalence of MS was 12.5 cases/100,000 inhabitants, with a predominance in females (71.4%) and Caucasoid (85.7%). The current average age was (43.8 ys). The most common initial symptom was sensory (40%), followed by optical neuritis (25.7%). Expanded Disability Status Scale average score was 2.4. The relapsing-remitting form was predominant (88.6%), most (74.3%) were on immunomodulatory treatment and (40%) had college education. CONCLUSION: Prevalence of MS in Uberaba (MG) is considered average in accordance to Kurtzke and Page and clinical features are consistent with most Brazilian studies.